2015
DOI: 10.1097/inf.0000000000000776
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Seven-valent Pneumococcal Conjugate Vaccine on Acute Otitis Media in Japanese Children

Abstract: After this research was completed, PCV7 was switched to a PCV13 that also contained serotype 3 and serotype 19A. We need to consider the possibility that serotype 15A, which is not included in PCV13, may increase and cause intractable AOM in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The high incidence of serotype 15A (8.9%) detected in our study is important since recent data have indicated that this serotype often colonizes vaccinated children and may cause multi-drug resistant Sp acute otitis media [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 77%
“…The high incidence of serotype 15A (8.9%) detected in our study is important since recent data have indicated that this serotype often colonizes vaccinated children and may cause multi-drug resistant Sp acute otitis media [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 77%
“…The strain with LVFX MIC of 64 mg/mL was also resistant to ABPC, CTRX, and MINO, and intermediate to STFX, IPM and CAM. There are reports in Japan and the United Kingdom that, after the introduction of pneumococcal conjugate vaccines, multidrug-resistant serotype 15A increased [22,23], thus, there are concerns about multidrugresistant S. pneumoniae. QRDR alteration was found in 30.8% (61/198 strains) and 87.5% (21/24 strains) of LVFX-susceptible strains with LVFX MIC of 0.5e2 mg/mL in S. pyogenes and H. influenzae, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Deployment of PCV7 was followed by increased prevalence of serotype 19A isolates, many of them multidrug-resistant, and, although serotype 19A is now covered by PCV13, a niche may be created for yet further types. Internationally, several groups have remarked on the increased prevalence of multidrug-resistant serotype 15A and 35B isolates [ 14 - 21 ] and a recent PHE analysis of invasive pneumococcal infections, using the data series of Table 3 , noted 15A to be among several serotypes now increasing in numbers and proportion in the UK [ 13 ]. The present analysis extends these findings, confirming that serotype 15A S. pneumoniae are of growing importance, as also shown (i) in the BSAC bacteraemia series ( Table 1 ), which overlaps the PHE series but also includes Scotland and Ireland, (ii) the BSAC series LRTI ( Table 2 ), which is the sole UK surveillance to test S. pneumoniae from their predominant disease setting, and (iii) among PHE reference submissions, which provide a rolling snapshot of resistance phenotypes causing concern to microbiologists at sending laboratories, which are predominantly in England, Wales and Northern Ireland, although with a few isolates received from elsewhere ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Again, however, rises are being seen in other, non-vaccine, serotypes, principally 8, 10A, 12F, 15A and 24F [ 13 ]. Serotype 15A is of particular interest since multidrug-resistant isolates belonging to this serotype have been reported as far apart as east Asia [ 14 - 16 ], North America [ 17 , 18 ], Norway [ 19 ], Italy [ 20 ] and Australia [ 21 ]. Here, we explore the rise of serotype 15A S. pneumoniae in the UK and Ireland at epidemiological and molecular levels, using data from both the British Society for Antimicrobial Chemotherapy (BSAC) and Public Health England (PHE) surveillances.…”
Section: Introductionmentioning
confidence: 99%